Peran Kepala Madrasah Sebagai Supervisor dalam Peningkatan Kinerja Guru - Mar’atul Azizah; Miranda Nur Apdila (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2021)
The purpose of this study was to describe the role of the principal as a supervisor at MA Roudlotul Ulum Mojoduwur Jombang. This study uses qualitative research which is a field research because the data generated is in the form of written words from objects and observable behavior. Qualitative research examines participant perspectives with multiple interactive strategies, such as direct observation, participatory observation, in-depth interviews, documents, complementary techniques, such as photographs, recordings and others. The results showed that the role of the principal as a supervisor at MA Roudlotul Ulum Mojoduwur Jombang in improving teacher performance by directing and guiding teachers during times of difficulty in the learning process there were several roles of the principal in improving teacher performance at MA Roudlotul Ulum. The teacher's performance is quite good but some are lacking due to limited facilities, such as when teaching in the classroom the teachers do not use learning media. Based on the results of research on the role of the principal as a supervisor in improving teacher performance at MA Roudlotul Ulum Mojoduwur Jombang, it can be concluded that the principal as a supervisor in improving teacher performance really makes a good contribution to the progress of the quality of learning so that it can encourage the performance of educators which is the key to success. in the world of education.